The Peter Townsend reader - Townshend, Pete 1945- (Policy, 2010)
This reader brings together a collection of Peter Townsend's most distinctive work. It allows readers to review the changes in social policy that have taken place nationally and internationally over the past six decades, and provides an insight into the development of one social scientist's entire intellectual approach.